Extreme emission of N2O from tropical wetland soil (Pantanal, South America) - Liengaard, Lars (2013)
Nitrous oxide (N2O) is an important greenhouse gas and ozone depleter, but the global budget of N2O remains unbalanced. Currently, ∼25% of the global N2O emission is ascribed to uncultivated tropical soils, but the exact locations and controlling mechanisms are not clear. Here we present the first study of soil N2O emission from the Pantanal indicating that this South American wetland may be a significant natural source of N2O. At three sites, we repeatedly measured in situ fluxes of N2O and sampled porewater nitrate (NO3-) during the low water season in 2008 and 2009. In 2010, 10 sites were screened for in situ fluxes of N2O and soil NO3- content. The in situ fluxes of N2O were comparable to fluxes from heavily fertilized forests or agricultural soils. An important parameter affecting N2O emission rate was precipitation, inducing peak emissions of >3 mmol N2O m−2 day−1, while the mean daily flux was 0.43 ± 0.03 mmol N2O m−2 day−1. Over 170 days of the drained period, we estimated non-wetted drained soil to contribute 70.0 mmol N2O m−2, while rain-induced peak events contributed 9.2 mmol N2O m−2, resulting in a total N2O emission of 79.2 mmol N2O m−2. At the sites of repeated sampling, the pool of porewater nitrate varied (0.002-7.1μmolNO3-gdW-1) with higher concentrations of NO3- (p < 0.05) found in drained soil than in water-logged soil, indicating dynamic shifts between nitrification and denitrification. In the field, O2 penetrated the upper 60 cm of drained soil, but was depleted in response to precipitation. Upon experimental wetting the soil showed rapid O2 depletion followed by N2O accumulation and a peak emission of N2O (2.5 - 3.0mmolN2Om-2day-1). Assuming that the observed emission of N2O from these wetland soils is generally representative to the Pantanal, we suggest that this undisturbed tropical wetland potentially contributes ∼1.7% to the global N2O emission budget, a significant single source of N2O.